Representasi Kekerasan Orangtua Terhadap Anak Dalam Film My First Client (2019) - Salsabila, Apriliana Salma; Baharuddin, Nalfaridas; Dadan, Sulyana (Fakultas Ilmu Budaya, Universitas Jambi, 2023)
This study analyses the representation of parental violence against children in the film